The Drosophila melanogaster Na+/Ca2+ Exchanger CALX Controls the Ca2+ Level in Olfactory Sensory Neurons at Rest and After Odorant Receptor Activation - Halty-deLeon, Lorena; Hansson, Bill S.; Wicher, Dieter (Frontiers in Cellular Neuroscience, 2018)
CALX, the Na+/Ca2+ exchanger in Drosophila, is highly expressed in the outer dendrites of olfactory sensory neurons (OSNs) which are equipped with the odorant receptors (ORs). Insect OR/Orco dimers are nonselective cation channels that pass also calcium which leads to elevated calcium levels after OR activation. CALX exhibits an anomalous regulation in comparison to its homolog in mammals (NCX): it is inhibited by increasing intracellular calcium concentration [Ca2+]i. Thus, CALX mediates only Ca2+ efflux, not influx. The main goal of this study was to elucidate a possible role of this protein in the olfactory response. We first asked whether already described NCX inhibitors were capable of blocking CALX. By means of calcium imaging techniques in ex-vivo preparations and heterologous expression systems, we determined ORM-10962 as a potent CALX inhibitor. CALX inhibition did not affect the odor response but it affected the recovery of the calcium level after this response. In addition, CALX controls the calcium level of OSNs at rest.